2010
DOI: 10.1042/cs20090554
|View full text |Cite
|
Sign up to set email alerts
|

ACE2–angiotensin-(1–7)–Mas axis in renal ischaemia/reperfusion injury in rats

Abstract: AngII (angiotensin II), ACE (angiotensin I-converting enzyme) and the AT1 receptor (AngII type 1 receptor) are associated with the inflammatory process and microvascular dysfunction of AKI (acute kidney injury) induced by renal I/R (ischaemia/reperfusion). However, Ang-(1-7) [angiotensin-(1-7)], ACE2 (angiotensin I-converting enzyme 2) and the Mas receptor also play a role in renal disease models. Therefore, in the present study, we have examined the renal profile of Ang-(1-7), ACE2 and the Mas receptor in ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
95
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 41 publications
12
95
0
1
Order By: Relevance
“…The data in that study also showed that the biphasic effect of ANG-(1-7) on the Na+/H+ exchanger occurred via the Mas receptor and that A779 (a Mas receptor antagonist) abolished this hormonal biphasic effect. These results are also consistent with previously described findings in the literature that indicated that the renal effects of ANG-(1-7) are dose dependent and mediated, at least in part, by the Mas receptor [193][194][195][196]. Nevertheless, in isolated rat proximal straight tubules (S3 segment), it was shown that, like ANG II, ANG-(1-7) exerts a biphasic effect through AT1 receptors: at physiological levels, ANG-(1-7) increases fluid and bicarbonate reabsorption, while at high concentrations, ANG-(1-7) decreases these parameters [183].…”
Section: Actions Of Ang-(1-7) In the Kidneysupporting
confidence: 82%
“…The data in that study also showed that the biphasic effect of ANG-(1-7) on the Na+/H+ exchanger occurred via the Mas receptor and that A779 (a Mas receptor antagonist) abolished this hormonal biphasic effect. These results are also consistent with previously described findings in the literature that indicated that the renal effects of ANG-(1-7) are dose dependent and mediated, at least in part, by the Mas receptor [193][194][195][196]. Nevertheless, in isolated rat proximal straight tubules (S3 segment), it was shown that, like ANG II, ANG-(1-7) exerts a biphasic effect through AT1 receptors: at physiological levels, ANG-(1-7) increases fluid and bicarbonate reabsorption, while at high concentrations, ANG-(1-7) decreases these parameters [183].…”
Section: Actions Of Ang-(1-7) In the Kidneysupporting
confidence: 82%
“…Angiotensin II increases and angiotensin 1-7 decreases in kidney tissue after ischemia reperfusion injury in rats (28,29). Interestingly, intrarenal angiotensin II concentration strongly correlates with urinary angiotensinogen concentration but is not correlated with plasma angiotensinogen, which implies that elevated urinary angiotensinogen reflects activation of the intrarenal RAS (30).…”
Section: Discussionmentioning
confidence: 80%
“…Alenina et al (2008) reported that Mas mRNA is predominantly found in the renal cortex of male mice. Indeed, functional Mas is detected in proximal tubules, as well as in the afferent arterioles, collecting ducts and the thick ascending limb of Henle and its expression is upregulated in renal ischemia (Ren et al 2002, Gwathmey et al 2010, Silveira et al 2010, Zimmerman & Burns 2012.…”
Section: Vascular Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 99%